Sistem Informasi Akuntansi, Efektivitas Pengendalian Internal, Asimetri Informasi dan Moralitas Individu terhadap Kecurangan Akuntansi - Riyan Adinugroho; Endah Susilowati (IPM2KPE, 2022)
The purpose of this research is to examine the influence of accounting information systems, the effectiveness of internal control, information asymmetry and individual morality on accounting fraud in . The population of this study were employees of PT. Petrokimia Gresik and the sampling technique used in this research is saturated sampling with a total sample of 100 employees of PT. Gresik Petrochemicals. Data was collected by giving questionnaires to respondents in departments related to accounting information systems. The data analysis technique used is the PLS Model with the help of Warp PLS 8.0 software which includes three stages in its measurement, namely outer model analysis, inner model analysis and hypothesis testing. The results of this study indicate that partially accounting information system variables, the effectiveness of internal control, and individual morality have a significant negative effect on accounting fraud. Meanwhile, information asymmetry has a significant positive effect on accounting fraud.